Case Study: Blended Learning Approach in Pool Lifeguard Training - Jackson, Shaun David (International Journal of Advanced Corporate Learning (iJAC), 2020)
The Pool Lifeguard Skill Set (SISSS00111), recognised across Australia, is targeted at those that wish to be professionally certified as a Pool Lifeguard in Australia. Incorporating risk management, supervision, communication, aquatic rescue and emergency care training, the audience covers a broad demographic in city and regional locations. The course has traditionally been taught through pre-course workbooks, reference to a manual, and face-to-face training sessions. While this traditional approach has been effective, Royal Life Saving wished to offer a more engaging and memorable pre-course delivery method. The goal was to enable students to arrive at the face-to-face training with a stronger, more embedded knowledge of key concepts and principles and allow for more face-to-face training time to be devoted to becoming proficient in the role’s important practical skills, such as aquatic rescue, first aid and advanced CPR. Hence, a project to develop an e-learning blended delivery solution was undertaken. The intention was that the online component of the course be completed prior to the face-to-face training and that it should augment the lifeguarding manual. It was also important that it is highly learner-centred, requiring learners to interact with the screens in order to access the key content and that it is a visually pleasing product with a quality aesthetic design.